Implementation Of Free Trademark Registration Facilitation For MSMe’s In Surabaya - Aulia Rahmah Hidayat; Muhammad Agus Muljanto (UNIVERSITAS PAKUAN, 2026)
. Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in regional economic development; however, the administrative process of trademark registration remains underutilized among MSME actors. Limited understanding of registration procedures, document requirements, and trademark classification often becomes an obstacle to participation in the registration system. To improve administrative accessibility and encourage greater participation, the Surabaya City Government, through the Department of Cooperatives, Micro, Small and Medium Enterprises and Trade, implements a free trademark registration facilitation program for MSMEs. This study aims to analyze the implementation of the trademark registration facilitation system in Surabaya using George C. Edwards III’s policy implementation model, which includes communication, resources, disposition, and bureaucratic structure. This research employed a descriptive qualitative approach with data collected through interviews, observation, and documentation. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the implementation of the administrative registration system has been carried out relatively well but has not yet reached optimal performance. In the communication aspect, outreach activities and inter-agency collaboration have supported information dissemination, although many MSMEs still encounter difficulties in understanding registration procedures and trademark classification. Resource limitations, including restricted facilitation quotas and limited personnel, also affect service effectiveness. Meanwhile, responsive service practices, established operating procedures, and institutional coordination have contributed positively to administrative implementation. Strengthening communication, expanding service capacity, and improving administrative coordination are necessary to optimize trademark registration services for MSMEs.